Happy birthday Bad Kitty - Bruel, Nick. (New York : Roaring Brook Press, 2009)
Bad Kitty's birthday fun is disrupted when someone takes off with her parents and an unexpected guest arrives for the party.
"A Neal Porter book."
Horn Book
Publisher's Weekly
School Library Journal
Horn Book, April 2010
Kirkus Review, August 2009
Keywords: Birthdays -- Juvenile fiction; Human behavior -- Juvenile fiction; Kittens -- Juvenile fiction; Behavior -- Fiction; Birthdays -- Fiction; Cats -- Fiction; Birthdays -- Fiction; Cats -- Fiction; Human behavior -- Fiction